(untitled) (Journal of Engineering, 2019)
A time series analysis can help to observe the behavior of the system and specify the system faults. In addition, it also helps to explain the various energy flows in the system and further aid in reducing the thermodynamic losses. The intelligent supervisory LabVIEW software can monitor the incoming data from the system by using Arduino microcontroller and calculates the important parameters. Energy, exergy, and anergy analysis present in this paper to investigate the system performance as well as its components. To accomplish this, a 4-ton vertical split air conditioner based on vapor compression refrigeration cycle charged with refrigerant R-22 was modified for experimental analysis. The results showed that during 5400 secs of experimental study, the system shut down once by the software for 5 min. The volumetric and isentropic efficiencies of the compressor were 79.85 % and 64.48 % respectively. The maximum entropy generation was due to the compressor of 3.4 W/K while the maximum anergy was due to the condenser of 1.39 kW. The exergy efficiencies of the compressor, condenser, and the evaporator were 73.57, 40.18, and 47.45 % respectively. The system and Carnot COP were 2.53 and 4.9 respectively. The exergy efficiency of the air conditioning system was 48.7 %.